Learning from text, video, or subtitles: A comparative analysis. (January 2021) - Tarchi, Christian; Zaccoletti, Sonia; Mason, Lucia
Abstract: The present study investigated the influence of media (text, video, or subtitled video) on students' learning outcomes. Past studies have raised concerns about the effectiveness of learning from online videos over content-equivalent texts. Moreover, subtitled videos place additional demands on learning. Two-hundred and forty-seven undergraduate students were randomly assigned to a text, video, or subtitled-video condition, in a pretest, posttest, and delayed posttest design. The topic assigned was stem cells. Literal, inferential, and transfer questions were used to assess comprehension and learning outcomes. Results from the study confirmed the substantial equivalence of all conditions in immediate comprehension. Conversely, results confirmed the disadvantage of subtitled videos for deep learning outcomes. Highlights: Three learning modalities (video versus subtitled video versus text) were compared. Performance in immediate comprehension outcomes was equivalent across modalities. Calibration performance was equivalent across modalities. In the subtitle condition performance in transfer decreased over time.